Towards Sustainable Battery Recycling: A Carbon Footprint Comparison between Pyrometallurgical and Hydrometallurgical Battery Recycling Flowsheets - Gert Van Hoof; Bénédicte Robertz; Bart Verrecht (Metals, 2023)
The expected large growth in electric mobility presents challenges, such as requiring a very large amount of critical raw materials like nickel, cobalt, and lithium. Due to this expected growth significant amounts of production scrap from cell and battery manufacturing will be generated. Over the next decade, increasingly larger amounts of Li-ion batteries from electric vehicles will also reach their end-of-life. Hence, in order to close the loop, the development and industrialization of sustainable battery recycling flowsheets are key so that both production scrap and end-of-life batteries can be recycled back to their ‘battery grade’ building blocks. Battery recycling flowsheets are typically categorized into two categories: (1) ‘Pyro-Hydro’, a combination of battery smelting in a pyrometallurgical process, followed by the further refining of the alloy via hydrometallurgy; and (2) ‘(Thermo)mechanical-Hydro’, a combination of (thermo)mechanical pretreatment and further hydrometallurgical refining of the resulting black mass. In this paper, a carbon footprint analysis is presented comparing these two battery recycling approaches: ‘Pyro-Hydro’ and ‘Thermomechanical-Hydro’, taking into account the impact of the latest evolutions in process technology and efficiency. To facilitate this comparison, a prospective LCA was carried out for the respective flowsheets. The quantitative analysis shows that ‘Pyro-Hydro’ leads to the lowest overall carbon footprint but also that both ‘Pyro-Hydro’ and ‘Thermomechanical-Hydro’ flowsheets have their challenges and opportunities for decarbonization. The inclusion of the fate of side streams such as graphite and electrolyte in the analysis is shown to be critically important in order to gain an objective and complete view.